Knowledge of Oral and Dental Health Impacts the Oral Hygiene Index Simplified (OHI-S) of Primary School Children - Pudentiana Rr RE; Tedi Purnama; Emini; Siti Nurbayani Tauchid; Neni Prihatiningsih (Institute of Medico-legal Publications Pvt Ltd, 2021)
Primary school children are a vulnerable group to oral and dental diseases. Less of knowledge on dentalhealth will lead to bad dental and oral hygiene status resulting in debris and calculus. The OHI-S is an idealdental and oral hygiene check tool for assessing the oral hygiene of primary school children.This studyaims to analyzethe relationship of knowledge of dental and oral health toOral Hygiene Index Simplified inelementary school children. Method: this type of analytic observational study with cross sectional design.The research was conducted on the research carried out in class III students of SDN Perigi 03 PondokAren,South Tangerang City. Data collection with a questionnaire on dental health knowledge andOral HygieneIndex Simplified.Data analysis using Chi-Square. Result: Knowledge of oral health toOral Hygiene IndexSimplified indicates that the p-value 0.023 (p <0.05). Conclusion: there is a significant relationship betweenknowledge of dental and oral health toOral Hygiene Index Simplified in primary school children